1995
DOI: 10.1152/ajpendo.1995.268.1.e15
|View full text |Cite
|
Sign up to set email alerts
|

Codominant effects of the fatty (fa) gene during early development of obesity

Abstract: Expression of a single copy of the rat obesity fatty (fa) gene may affect energy balance. To test this hypothesis, the effects of zero, one, and two copies of fa on early growth were evaluated, using a molecular genetic method for counting fa alleles inherited by 7- and 14-day-old F2 offspring of a BN/Crl x Crl:ZUC-fa F1 intercross. Litter and sex effects were controlled by multiple-regression analysis, allowing genotype effects on the weights of body, inguinal adipose pads, interscapular brown adipose tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…The factor "sex" was not found to influence body mass growth significantly (P ϭ 0.42) of either MSG-treated or control pups. Least square means obtained by ANOVA of body mass measurements on day 10 showed for the controls that, in line with previous studies (18,38), average body mass of the females tended to be smaller (19.6 Ϯ 0.6 g) than that of the males (20.7 Ϯ 0.7), but MSG treatment reduced average body masses to virtually identical levels (17.4 Ϯ 0.5 g in females and 17.4 Ϯ 0.8 g in males). Similar to studies investigating other treatment factors and discussed previously (18), there were no significant interactions between treatment and the factors litter and sex.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The factor "sex" was not found to influence body mass growth significantly (P ϭ 0.42) of either MSG-treated or control pups. Least square means obtained by ANOVA of body mass measurements on day 10 showed for the controls that, in line with previous studies (18,38), average body mass of the females tended to be smaller (19.6 Ϯ 0.6 g) than that of the males (20.7 Ϯ 0.7), but MSG treatment reduced average body masses to virtually identical levels (17.4 Ϯ 0.5 g in females and 17.4 Ϯ 0.8 g in males). Similar to studies investigating other treatment factors and discussed previously (18), there were no significant interactions between treatment and the factors litter and sex.…”
Section: Methodssupporting
confidence: 91%
“…The program Statistica 5.5 (StatSoft, Tulsa, OK) was used for multifactorial analysis of variance (ANOVA) including factor repetition if required. In the analysis of the course of body mass development, the factors considered were treatment and age (repeated measurements), and in addition litter and sex, to take into account variabilities introduced by these parameters according to preceding investigations (18,38). Average data values were described by least square means (ϮSE) provided by ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies [16,30], when the data on body composition, body mass, FI, and MR of pups were evaluated, we took into account the considerable between-litter variability in growth [21,30,35] as well as the gender-related differences in these variables by considering a combined litter-gender effect as the second factor (besides treatment) in the two-way ANOVA statistics for each of the age groups. This was done by simply assigning different litter numbers to male and female littermates.…”
Section: Discussionmentioning
confidence: 99%
“…The Zucker rat has been recognized as a superior model to investigate effects of obesity on chronic disease development, including cancer (Bray, 1977;de Assis et al, 2006;Hakkak et al, 2007), but its utility for investigations of mammary carcinogenesis is limited due to scant epithelial development in mature mammary glands of obese as compared with lean counterparts (Hu et al, 2002). Since it was reported that young heterozygous lean Zucker (+/fa) rats demonstrate a number of differences from wild type lean Zucker (+/+) rats, e.g., higher body weights, fat cell size, inguinal fat pad weights, pad-to-body weight ratios, serum cholesterol, adipose tissue lipoprotein lipase and glycerol-3-phosphate dehydrogenase, hepatic and adipose tissue 6-phosphogluconate dehydrogenase activities and serum leptin levels (1.6 and 0.9 ng/ml in +/fa and +/+, respectively, ) Heo et al, 2002;Phillips and Cleary, 1994;Truett et al, 1995;Zhang et al, 1997), we here investigated whether they might provide the basis for a leptin-related mammary carcinogenesis model. Two independent experiments were performed.…”
Section: Introductionmentioning
confidence: 99%